Treatment of Adult Spinal Muscular Atrophy: Overview and Recent Developments - Brakemeier, Svenja; Stolte, Benjamin; Kleinschnitz, Christoph; Hagenacker, Tim (Current Pharmaceutical Design, 2022)
Spinal muscular atrophy (SMA) is a rare genetic neuromuscular disease leading to progressive and, in many cases, severe muscle weakness and atrophy in the natural disease course. An increasing number of gene-based treatment options have become available in recent years. Growing knowledge regarding the underlying genetic mechanisms makes the disease well amenable to them. Over the past few years, data on new treatments, their mechanisms of action and therapeutic outcomes have been published, reflecting the current dynamics in this field. With the approval of the antisense oligonucleotide nusinersen, the vector-based therapy with onasemnogene abeparvovec and the small molecule splicing modifier risdiplam, three gene therapeutic drugs are available for the treatment of SMA showing improvement in motor function. But in the pivotal studies, several relevant parameters have not been addressed. There is a data gap for the treatment outcome of adult individuals with SMA as well as for several other relevant outcome parameters, like bulbary or ventilatory function. With increasing treatment options, additional individual therapies have become necessary. Studies on combination therapies or switch of therapy, e.g., the sequential administration of onasemnogen abeparvovec and nusinersen, are necessary. An overview of current developments in the field of therapeutic options for adult SMA is presented. Important characteristics of each therapeutic options are discussed so that the reader can comprehend underlying pathophysiological mechanisms as well as advantages and disadvantages of each therapy. The focus is on gene-based treatment options, but options beyond this are also addressed.
Keywords: genotype-phenotype correlation